Chapter 5 The Communicative Constitution of the World A Luhmannian View on Communication, Organizations, and Society - Grothe-Hammer, Michael (Taylor & Francis, 2022)
This chapter introduces Niklas Luhmann's theory of organizations, which he conceived as communicatively constituted social systems that are created through decision-making. Decisions are thereby also understood as communicative events, ones that are inherently paradoxical as they attempt to select a certain option while simultaneously communicating discarded alternatives. Decisions are, hence, fragile events provoking opposition and rejection. Organizations can be understood as social phenomena that are capable of de-paradoxifying decisions by featuring these very decisions as their main mode of operation. However, Luhmann asserts that not only organizations, but our entire social world is constituted through communication. Against this backdrop, this chapter also highlights the role of macro-societal domains such as politics, science, economics, and love. Like organizations, these macro-societal domains can be understood as communicatively constituted systems that have certain characteristics and effects. In this respect, the Luhmannian framework offers a communication-based counterprogram to the mainstream debates of institutionalism.